(untitled) (Global Journal of Human-Social Science, 2013)
The study investigated the relationship between teacher’s questioning behaviour and instructional organization and students’ achievement in English Language. The study adopted a descriptive research design. Four Research Questions were answered. The participants were 30 English Language teachers and 450 students randomly selected from 15 Senior Secondary Schools. The instruments for data collection were Teachers’ Questioning Behaviour Observation Checklist (r=.79), Teachers’ Instructional Organization Observation Rating Scale (r=.81) and Achievement Test in English Language (r=.78). Findings revealed that teachers ask display and referential questions that are largely mono-directional. There is a positive, very strong relationship between Teachers’ Questioning Behaviour and students’ achievement in English Language. Teachers’ Instructional Organization has negative, very weak relationship with students’ achievement in English Language. It is recommended that teachers of English Language should structure questions specifically for the purpose of diagnosing students’ needs and for bridging learning gap among students in order to increase their performance in the subject. English Language teachers should attend, on regular basis, seminars, conferences and workshops that will expose them to proper deployment of questions and patterns of instructional organization in the classroom to optimize learning.